Tecnologias analítica e de produção vegetal da Quixabeira (Sideroxylon obtusifolium (Roem. e Schult.) Penn.) - Gomes, Azenate Campos (2021)
Sideroxylon obtusifolium (Roem & Schult.) T.D.Penn. is considered as one of the promising plants for the future, due to its high medicinal potential; however, the inadequate extraction of raw material for producing plant drugs has affected its population in natural systems, requiring studies to support its sustainable use. Thus, this study aimed to analyze the physical, chemical, and biological characteristics of S. obtusifolium under different environmental conditions and development stages, aiming at the production of standardized plant drugs. A phenological study was conducted with 30 specimens, analyzing their production in the Western and Eastern Cariri microregions in Paraíba State, Brazil, through the intensity and synchrony of the phenophases, biometric characterization, pre germinative treatments, vigor, and quality index of the specimens. Young specimens were analyzed in full and pruned conditions. Plant drugs were assessed as for particle size from the aerial part and stem periderm in different environments and development stages of young specimens, using different analytical techniques, thermal analysis (TG and DTA), morphological characterization of particles, and pharmacopeia physical characterization. Methods for the quantification of tannins and flavonoids in plant drugs from adult specimens from Sumé were developed and validated by UV/Vis spectrophotometry. These methods were co-validated in plant drugs from adult and young specimens from São João do Cariri, using fluid and dry nebulized extracts. The quantification of tannins and flavonoids was correlated with the evaluated ecological parameters. Specimens from Sumé and São João do Cariri have different phenological behavior, characterized by different responses to precipitation. Asynchronous and synchronous reproductive phenological events were observed in specimens from Sumé and São João do Cariri, respectively. The Dickson quality index of young individuals showed a positive correlation with the biometric data of seeds. Plant drugs with particles of 297–149 and 73–37 μm had different activation energies, which allowed the distinction of adult specimens from different environments. Enthalpy differentiated young individuals at different development stages in adult specimens. The morphological analysis showed high heterogeneity in the morphology, size, and distribution of sieved particles, demonstrating that the current technology of production and granulometric separation of medicinal plant drugs needs to be improved. The analytical method developed and validated for the quantification of tannins and flavonoids in plant drugs from Sumé is selective, linear, precise, accurate, and robust. The partial validation demonstrated linearity, precision, and accuracy in the samples from adult specimens and in fluid and dry nebulized extracts from young specimens in São João do Cariri. The extracts from the aerial part and stem peridermis had significant differences for tannins and flavonoids regarding particle size, different collection environments, and different development stages. The first two principal components accounted for more than 98% of the total variation in the assessed dataset. Seed mass and diameter, Dickson quality index, and fruiting contribute as indicators of tannin and flavonoid concentrations in all analyzed extracts. The data recorded for S. obtusifolium confirms that the use of stem periderm should be replaced by the cultivation of young individuals due mainly to the high content of flavonoids (89.54% more), contributing to the species sustainability.